Quenching correction for in vivo chlorophyll fluorescence acquired by autonomous platforms: A case study with instrumented elephant seals in the Kerguelen region (Southern Ocean) - Xing, X.; Claustre, H.; Blain, S.; D’Ortenzio, F.; Antoine, David; Ras, J.; Guinet, C. (American Society of Limnology and Oceanography, Inc., 2012)
As the proxy for Chlorophyll a (Chl a) concentration, thousands of fluorescence profiles were measured by instrumented elephant seals in the Kerguelen region (Southern Ocean). For accurate retrieval of Chl a concentrations acquired by in vivo fluorometer, a two-step procedure is applied: 1) A predeployment intercalibration with accurate determination by high performance liquid chromatography (HPLC) analysis, which not only calibrates fluorescence in appropriate Chl a concentration units, but also strongly reduces variability between fluorometers, and 2) a profile-by-profile quenching correction analysis, which effectively eliminates the fluorescence quenching issue at surface around noon, and results in consistent profiles between day and night. The quenching correction is conducted through an extrapolation of the deep fluorescence value toward surface. Asproved by a validation procedure in the Western Mediterranean Sea, the correction method is practical and relatively reliable when there is no credible reference, especially for deep mixed waters, as in the Southern Ocean. Even in the shallow mixed waters, the method is also effective in reducing the influence of quenching.